Differential factorization method APPLIED TO GeoecologICAL PROBLEMS - Babeshko, Vladimir Andreevich; Babeshko, Olga Mephodievna; Zaretskaya, Marina Valerievna; Kapustin, Mikhail Sergeevich; Shestopalov, Valeriy Leonidovich (Computational Continuum Mechanics, 2013)
The transport of substances in a block structure, where each block is a layer, and the settlement of these substances on a diverse-type base are considered. Such issues encountered in studying ecological, seismological, and materials science problems can be described by the mixed boundary-value problems of the same type. Application of a differential factorization method allows us to obtain an integral representation of the solution for each block. The results of calculations for the model problem are presented.
Keywords: substance transport; block structure; differential factorization method